Odpowiedzi

2010-03-07T12:54:16+01:00
4x-y=8 6x-5y=-5
8x-2y=16 5x+6y=6

4x-y=8
6x-5y=-5

4x = y+8 => x = y/4 + 2

6(y/4 + 2)-5y=-5
2,5y + 12 - 5y - -5
-2,5y = -17
x= y/4+8
---------------
y = 6,8
x= 35,2
------------------
8x = 2y+16
6y=-5x+6

x = y/4 + 2

y=-5x+6/6

x=((-5x+6)/6)/4+2

x=-5x/24 + 1/4 + 2
24x/24-5x/24 = 2,25

19/24x=2,25 /*24
19x = 54


y=-5(54/19)+1
y=-54/95+1 =>
----------------
y=41/95
x= 54/19
---------------





Najlepsza Odpowiedź!
2010-03-07T12:59:20+01:00
4x-y=8/*(-5)
6x-5y=-5
-20x+5y=-40
6x-5y=-5

-14x=-45/:-14
x=3 całe i 3/14


8x-2y=16/*3
5x+6y=6
24x-6y=48
5x+6y=6
29x=54/:29
x=1 całe i 25/29